The Role Of Public Relations In Building a Positive Image of an Organization - Lativah, Fauziah; Razali, Geofakta (Semantik: Journal of Social, Media, Communication, and Journalism, 2023)
Positive images are not formed immediately or by chance, but through a process and strategy. To achieve these goals and objectives requires an art to create a better public understanding so as to deepen public trust in an individual / organization. Public relations is applied to support product promotion activities and image creation. The role of public relations is able to contribute in shaping the corporate image by giving positive projections about its products. If the company's image is positive, then public relations has succeeded in improving the image of the company it represents. Conversely, if the image obtained by a company is negative, then public relations needs to try to restore the negative image into a positive image so that the company can again get a positive image in the eyes of consumers. with public relations, efforts to develop a company's image to become more comprehensive. Consumers tend to want to consume products / services from producers who can be trusted, have a positive image and are able to communicate well with stakeholders